Trefoil factor-3 is not a useful marker of mucosal healing in Crohn's disease treated with anti-TNF-α antibodies - Eder, Piotr (World J Gastroenterol, 2017)
AIM: To evaluate whether repeated serum measurements of trefoil factor-3 (TFF-3) can reliably reflect mucosal healing (MH) in Crohn’s disease (CD) patients treated with anti-tumor necrosis factor-α (anti-TNF-α) antibodies. METHODS: Serum TFF-3 was measured before and after anti-TNF-α induction therapy in 30 CD patients. The results were related to clinical, biochemical and endoscopic parameters. MH was defined as a ≥ 50% decrease in Simple Endoscopic Score for Crohn’s disease (SES-CD). RESULTS: SES-CD correlated significantly with CD clinical activity and several standard biochemical parameters (albumin, leukocyte and platelet counts, C-reactive protein, erythrocyte sedimentation rate, fibrinogen). In contrast, SES-CD did not correlate with TFF-3 (P = 0.54). Moreover, TFF-3 levels did not change significantly after therapy irrespectively of whether the patients achieved MH or not. Likewise, TFF-3 did not correlate with changes in fecal calprotectin, which has been proposed as another biochemical marker of mucosal damage in CD. CONCLUSION: Serum TFF-3 is not a convenient and reliable surrogate marker of MH during therapy with TNF-α antagonists in CD.